VALIDITY OF AUTHENTIC DEED MADE BY NOTARY IN SUSPECT STATUS - I Putu Adi Tanaya (NOTARIIL Jurnal Kenotariatan, 2023)
The Notary in making an authentic deed as a general official applies to that, even though he is not involved in the forgery that occurs in the authentic deed, the Notary can be summoned by the Indonesian National Police as a witness. then it turns out that sufficient original evidence is found for the involvement of the Notary, then it is possible that the Notary can be made a suspect. As long as the Notary is in the status of a suspect, how is the legal protection for a Notary suspected of committing a criminal act? how is the validity of the deed made by a notary in the status of a suspect? The purpose of this study is to find out how is the protection of a notary who is suspected of committing a criminal act and the validity of an authentic deed made by a notary who is currently in the status of a suspect. This study uses a normative juridical method. In accordance with the applicable law, legal protection for a Notary is in the right of notarizing a Notary and also the procedure for summoning a Notary. A notary is in suspect status if he continues to make a deed because of the absence of a notary in making a deed, he is in the status of not being dismissed, suspended (suspended), fired and retired. Notary as after the suspect is not necessarily guilty and the principle of presumption of innocence must be upheld, until a court decision has definite legal force. It depends on the community still willing to use the services of a notary who is in the status of a suspect or not.